AÇIK VE KAPALI BURUN AMELİYATI İNSİZYONLARININ BURUN UCU KANLANMASI VE BURUN UCU ÖDEMİ AÇISINDAN KARŞILAŞTIRILMASI - KARASU, NECMETTİN (Fırat Üniveristesi, 2011)
Bu çalışmanın amacı, açık ve kapalı burun ameliyatı insizyonlarının burun ucu ödemi ve burun ucu kanlanmasına olan etkilerini araştırmak. Yöntemler arasında bu açılardan fark olup olmadığını objektif olarak ortaya koymaktır.Araştırma gruplarına 12'si açık, 12'si kapalı toplam 24 hasta alındı. Açık grubun yaş ortalaması 28,1±5,3 iken kapalı grubun yaş ortalaması 22,7±5,2 idi. Her iki grubun %75'i kadın ve %25'i erkekti. Grupların preoperatif ve postoperatif 1. hafta, 1. ay, 3. aylarda doppler ultrsonografi ile burun ucu ödemi ve arteriyel kan akımı ölçüldü.Hastaların her takibinde burun ödemini değerlendirmek için önceden seçilen noktalarındaki cilt kalınlığı ölçüldü. Hastaların preoperatif ve postoperatif değerlendirmelerinde her iki grup arasında ödem açısından istatistiksel olarak anlamlı fark yoktu. Her iki grupta en fazla 1. haftada olmak üzere postoperatif ödem gözlendi. Sağ tip defining point ve sol tip defining point noktalarındaki ödemin azalarak 3. ayın sonunda kaybolduğu gözlendi. Sadece açık teknikteki hastaların riniyon noktasındaki ödemin belirgin olarak azalmasına rağmen 3. ayın sonunda devam ettiği görüldü. Her iki gruptaki hastaların tüm kontrollerinde önceden belirlenen noktalardaki arteriyel kan akımı ölçüldü. Her iki grup arasında kanlanma açısından istatistiksel olarak anlamlı fark yoktu. Sadece kapalı gruptaki hastaların arteriyel kan akımı parametrelerinden bazılarında fark gözlendi. Bunun muhtemel sebebi; Açık teknikte tüm disseksiyonlar muskuloaponevrotik tabaka altından görerek yapıldığından majör bir artere hasar verilmemesi, ancak kapalı teknikte net bir cerrahi görüş sahası olmadığından majör bir arterin yaralanmış olmasından olabilir.Açık ve kapalı burun ameliyatı yapılan hastalarda ödem ve kanlanma açısından anlamlı bir fark olmadığını, bunun da teknik seçimini etkilememesi gerektiği sonucuna varıldı.Anahtar Kelimeler: Burun Ucu, Ödem, Kanlanma, İnsizyonlar

The aim of the present study was to investigate the effects of open and closed nasal surgery incisions on edema and blood flow of the nasal tip. It was also aimed to clarify if there were differences in edema and blood flow of the nasal tip between these techniques.The study comprised two groups of patients, open nasal surgery group (n=12) and closed nasal surgery group (n=12). The mean ages of the patients in the open and closed nasal surgery groups were 28,1±5,3 and 22,7±5,2 respectively. In both groups, the percentages of the man and women patients were 25% and 75%. The degree of edema and rate of the blood flow of the nasal tip were measured using doppler ultrasonography preoperatively and postoperatively at the ends of the first week, first month and third month.In the followup examination of the patients, the thickness of the nasal skin in the predetermined points of the nose were measured in order to evaluate the degree of edema. In the preoperative and postoperative evaluation of the patients, there was no statistical difference in the degree of edema between the two groups. In both groups, postoperative edema were observed, which was particularly more obvious in the first week. The degree of the edema was progressively decreased, disappearing at the end of the third month in the right and left defining points. Only in the patients in open surgery group, the degree of edema in the riniyon point was decreased prominently, there were stil edema to small extents at the end of the third mont though. In the all followup examinations of the patients from the both groups, the rate of blood flow was measured in the predetermined points of the nasal tip. There was no statistical difference in the rate of blood flow between the groups. Only in the patients from closed nasal surgery group, there were statistical differences in some parameters associated with the arterial blood flow. The underlying mechanism for this might probably be due to that in the open technique, all the dissections were performed with visual guidance under musculoaponeurotical layer, therefore, major arteries could probably be protected from damages. However, in the closed technique, there was a higher possibility of damages to major arteries, since the surgery field could not be seen clearly.It was concluded that there was no significant differences in the degree of edema and the rate of blood flow between the patients undergone open and closed nasal surgery, therefore, these parameters should not influence the preference of open or closed nasal surgery techniques.Keywords: Nasal tip, edema, blood flow, incisions
Evaluatıon of the effects of open and closed nasal surgery ıncısıons on edema and blood flow of the nasal tıp
Keywords: Plastik ve Rekonstrüktif Cerrahi